Site visit by MTUN COE Secretariat - Putra Mohd Darul Ridzuan, Rosli (Penerbit UMP, 2014)
A site visit was organised by the MTUN COE Secretariat on April 9, 2014. The objective of the visit was to see the progress of research works carried out under the MTUN COE Grant. A consultation service was also conducted.